A System Is Not a Product. (Communications of the ACM, 2012)
The author argues that clocksource.h in Linux software systems is an example of good code, and answers a letter from a reader concerning network monitoring software that requires configuration information reentry following system upgrades. Topics include layering violations, cyclecounters in codes for the tracking of time, and the difference between systems that require maintenance and products and appliances that require only human interface. Unix operating systems and the iPhone music storage product are mentioned.